OF–CEAS laser spectroscopy to measure water isotopes in dry environments: example of application in Antarctica - T. Lauwers; E. Fourré; O. Jossoud; D. Romanini; F. Prié; G. Nitti; M. Casado; K. Jaulin; M. Miltner; M. Miltner; M. Farradèche; V. Masson-Delmotte; et al. (Atmospheric Measurement Techniques)
Water vapour isotopes are important tools to better understand processes governing the atmospheric hydrological cycle. Their measurement in polar regions is crucial to improve the interpretation of water isotopic records in ice cores. In situ water vapour isotopic monitoring remains challenging, especially in dry places of the East Antarctic Plateau, where water mixing ratios can be as low as 10 ppm. We present in this article new commercial laser spectrometers based on the optical-feedback cavity-enhanced absorption spectroscopy (OF–CEAS) technique, adapted for water vapour isotopic measurements in dry regions. We characterise a first instrument adapted for Antarctic coastal monitoring with an optical cavity finesse of 64 000 (ring-down time of 54 µs), installed at Dumont d'Urville Station during the summer campaign 2022–2023, and a second instrument with a high finesse of 116 000 (98 µs ring-down time), to be deployed inland of East Antarctica. With a drift calibration every 24 h, the stability demonstrated by the high-finesse instrument allows one to study isotopic diurnal cycles down to 10 ppm humidity for δD and 100 ppm for δ18O.